DEVELOPMENT OF LATENT FINGERPRINTS USING NON-CONVENTIONAL POWDER METHODS - Prasad , Sreelakshmi; Soman, Surya; Christal L , Gloria (Journal of Forensic Medicine and Toxicology, 2024)
Fingerprints, a crucial form of evidence frequently encountered at crime scenes, exist in various forms: latent, patent, and plastic, with latent prints being the most common. The successful recovery of these prints relies on advanced fingerprint development methods, which have surpassed traditional techniques due to modern technological advancements. Investigative methods continue to evolve, significantly enhancing the efficiency of case resolution. A wide array of development techniques is available, with unconventional powder methods emerging as safe and effective approaches for fingerprint retrieval. The current study developed 30 fingerprint samples from five different non-porous surfaces using five distinct, readily accessible powders. This study focused on powders like talcum powder, turmeric powder, fullers earth powder, coffee powder, naphthalene balls powder and non-porous surfaces like steel, glass, ceramic, wood, and plastic to highlight the effectiveness of powder based techniques. The results were apparent, showing clear ridge formation enabling the identification of the collected fingerprints.
Keywords: Fingerprints; Development; Porous surface